KINERJA GURU BERSERTIFIKAT PENDIDIK - Lukman Lukman Lukman (Manajer Pendididikan, 2016)
The purpose of the research to evaluate the performance of certified teacher’s educator. The subject of this research was the teachers who has certified teacher’s educator in Muhammadiyah Senior High School Number 4 Bengkulu City. The technique of collecting data was interview, observation, and study documentation. Technique of analyze data was qualitativeand quantitative. such as reduction of, display data, and got conclusion or verification, so that can be seen teacher performance who has certified teacher’s educator in Muhammadiyah Senior High School Number 4 Bengkulu City and also follow-up toward that result. The Result is good Based on this research, can be concluded that the performance of teacher’s has reached suitable result.Keyword: performance, certified teacher’s educator.